Short‐term variation in leaf‐level water use efficiency in a tropical forest. Issue 6 (9th January 2023) - Davidson, Kenneth J.; Lamour, Julien; Rogers, Alistair; Ely, Kim S.; Li, Qianyu; McDowell, Nate G.; Pivovaroff, Alexandria L.; Wolfe, Brett T.; Wright, S. Joseph; Zambrano, Alfonso; Serbin, Shawn P.
Summary: The representation of stomatal regulation of transpiration and CO2 assimilation is key to forecasting terrestrial ecosystem responses to global change. Given its importance in determining the relationship between forest productivity and climate, accurate and mechanistic model representation of the relationship between stomatal conductance ( g s ) and assimilation is crucial. We assess possible physiological and mechanistic controls on the estimation of the g 1 (stomatal slope, inversely proportional to water use efficiency) and g 0 (stomatal intercept) parameters, using diurnal gas exchange surveys and leaf‐level response curves of six tropical broadleaf evergreen tree species. g 1 estimated from ex situ response curves averaged 50% less than g 1 estimated from survey data. While g 0 and g 1 varied between leaves of different phenological stages, the trend was not consistent among species. We identified a diurnal trend associated with g 1 and g 0 that significantly improved model projections of diurnal trends in transpiration. The accuracy of modeled g s can be improved by accounting for variation in stomatal behavior across diurnal periods, and between measurement approaches, rather than focusing on phenological variation in stomatal behavior. Additional investigation into the primary mechanisms responsible for diurnal variation in g 1 will be required to account for this phenomenon in land‐surface models.